Readiness of Tourism Branding in Supporting Smart Branding of Ambon City - Wa Ode Sitti Jurianti Aswad; Stevianus Titaley (International Journal of Science and Society, 2023)
One of the dimensions of smart city is smart branding where one of the elements is tourism branding. Tourism branding can be interpreted as an effort to make the city a tourist destination that has an identity and character so that it has a strong appeal. Ambon City, which is starting a smart city program with all the potential and problems, is faced with challenges in meeting the readiness of the smart city implementation as a whole. This study aims to identify and analyze the readiness of tourism branding in Ambon City by examining several indicators, namely facilities that support tourist comfort (amenities), accessibility, ancillary services and hospitality. The analysis method used in this research is descriptive qualitative. The results of the analysis show the unpreparedness and need for development of several indicators of tourism branding such as road conditions and transportation access to tourist attractions, availability of eating spots and lodging, availability of tour guide services, travel agents, and tourist information. However, some things have started positively such as promotional innovations and tourist services that utilize information technology.